The Role of Hadith in Character and Moral Formation - Ahyat Halimi; Ahmad Mohammad Tidjani (Penerbit Hellow Pustaka, 2025)
This article discusses the role of hadith in shaping the character and morals of students and its relevance to character education in Indonesia. As the primary source of Islamic teachings, hadith provides a strong moral foundation, particularly in the aspects of honesty, trustworthiness, compassion, and social concern. By examining various hadiths on noble morals, hadith-based character education is believed to be able to provide solutions to the moral crisis facing modern society. The research method used is a literature study with a qualitative approach, namely reviewing literature, hadith books, and relevant previous research. The results of the study indicate that the implementation of hadith in character education is not only normative but also applicable in building a generation with noble morals. This article emphasizes the importance of integrating hadith into the curriculum of Islamic education and general education to strengthen character education in the era of globalization.